Contemporary perspectives on research on motivation in early childhood education - Saracho, Olivia N. (Contemporary perspectives in early childhood education., 2019)
"This volume is devoted to understanding mutual and contemporary themes in the individuals' motivation and its relationship to cognition. The current literature covers several methods to the multifaceted relationships between motivational and cognitive processes. Comprehensive reviews of the literature focus on prominent cognitive perspectives on motivation with young children, which includes ages from birth to eight years of age. The chapters in this special volume reviews and critically analyze the literature on several aspects of the relationships between motivational and cognitive processes and demonstrate the breadth and theoretical effectiveness of this domain. This brief introduction acknowledges the valuable contributions of these chapters to the study of human motivation. This volume can be a valuable tool to researchers who are conducting studies in the motivation field. It focuses on important contemporary issues on motivation in early childhood education (ages 0 to 8) to provide the information necessary to make judgments about these issues. It also motivates and guides researchers to explore gaps in the motivation literature"--